Unidirectional synchronization of two multiscroll chaotic systems using nonlinear control technique - Razminia, A. (Нелінійні коливання, 2013)
The dynamics of nonlinear systems and especially chaotic ones have attracted increasing attention in recent years. In this paper, we consider a new chaotic system that recently introduced in the literature. This system exhibits several various behaviors such as two, three, and four scrolls. Using a nonlinear control methodology, we synchronize a unidirectional coupling structure for the two chaotic systems. Numerical simulations are used to support the theoretical analysis. Additionally we see the robustness of the system in the presence of a noise in simulation.